Factors influencing location choice and cluster pattern of manufacturing small and medium enterprises in cities: Evidence from Khulna City of Bangladesh - S. M. Towhidur Rahman; Ahsanul Kabir (Journal of Global Entrepreneurship Research, 2019)
This study aims to identify the location and cluster pattern of manufacturing SMEs in Khulna City and the reasons behind such pattern since localisation of SMEs has significant impact on the economic development of cities and regions. A walking survey was conducted to identify the SME location pattern and a semi-structured personal interview was conducted to collect data from manufacturing SME entrepreneurs to find why such patterns exist. A cross section qualitative multiple case study design and pattern matching technique was applied to answer the research questions. The finding of the study shows SME location choice was influenced by a combination of location specific, personal, and community factors whereby personal factors are prioritised over other factors in location selection. While the cluster formation or localisation of SMEs depends on only location-specific factors. The study findings are expected to contribute in urban planning and regional development through providing useful insights relating allocation of spaces for industry development.
Keywords: 650; SME; Location theory; Cluster; Manufacturing industry; Personal factor; Bangladesh